Lesser omentum epithelioid leiomyosarcoma - Plazzotta, Cecilia; Rondan, Mariela; Rodríguez, Gustavo; Vaz, Dinorah; Ruso, Luis (Cirugía del Uruguay, 2003)
Primitive tumors of epiploon are rare, the nost requent being those of the sooth muscles (39%) with predominance among the latter of mailgnant tumors (63%). The onset may be at any age, the greatest incidence occuring between the 4th and 6th decade of life and in males.